Digitalisasi Perusahaan Untuk Meningkatkan Kinerja Karyawan - Wibowo, Purnomo Ari; Sulistyowati, Sulistyowati; Sumantri, Andar Sri; Ngaijan, Ngaijan; Santoso, Kurniawan Teguh; Jumaizi, Jumaizi; Supriyanto, Supriyanto; Roesjanto, Roesjanto (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
There are so many companies nowadays, some are large companies and some are small companies. Every company certainly hopes to continue to exist in an era of intense competition. Without realizing it, technology is also experiencing rapid development too. The problem faced by companies is how to improve employee performance with current technology. The company realizes that employee performance is very important so that the company can compete with other companies. One way to improve company performance is by digitalizing the company. Steps that companies can take in implementing company digitalization are: creating a business website, carrying out digital marketing, implementing cloud computing, utilizing big data, implementing AI technology, and participating in digital training for their employees.